Foules, espaces publics urbains et apprentissage de la co-présence chez les adolescents des quartiers populaires d’Ile de France - Nicolas Oppenchaim (Conserveries Mémorielles)
This article aims at further documenting the relationship of teenagers to the urban crowd. This issue will be addressed in three stages. First and foremost, we shall outline - after the work of Isaac Joseph - the reasons why the transition from the crowd to the public is one of the main features of contemporary societies. This transition refers both to the metaphorical space of collective mobilizations as well as to the urban space. Characteristically, large crowds overwhelmed by emotions do not define large cities. Public spaces do, for they are places of co-presence organized around civil inattention. These spaces thus offer opportunities to meet other city-dwellers while guaranteeing a right to privacy. However, we shall then demonstrate that this quiet perception of large gatherings in the city is not self-evident, and so during adolescence, notably. It will therefore be necessary to introduce the problem of learning in our reflections upon urban public spaces. Thus, some of the teenagers residing in the popular districts of the Ile-de-France express a fear of urban crowds very much akin to that developed in the speeches of the 18th and 19th centuries. Broadly speaking, teenagers from popular districts differ in their speeches through four ideal-typical perceptions of the crowd: ‘the potentially entertaining crowd’, ‘the indifferent crowd’, ‘the threatening crowd’ or ‘the public space crowd.’ We shall eventually see that these different perceptions of teenagers are to be related to their relationships to their neighbourhoods and their own learning of mobility.